E-Supervision as Tool for Quality Assurance in School Administration: Implications for Nigerian Supervisors - Awulor-Hephzibah, B.N. (International Journal of Educational Management, 2022)
The world is currently driven by information and communication technology (ICT), thereby compressing the globe into a village. ICT facilities have become relatively affordable for almost every organisation, including the schools. The introduction of technologies into the school system is creating complex issues for non-ICT supervisors. As professionals who are expected to guide and support the new generation of learners as well as teachers, supervisors need to match-up with the trend. Traditional supervisory tool is fast giving way to ICT-enabled supervision. This paper deals with quality assurance benefits for e-supervision in the school system, with specific focus on its implications for Nigeria school supervisors. The paper acknowledges that the main policy objective in education in Nigeria is to raise the quality of education at all levels in order to make the products of the system more useful to themselves and the society at large. Quality assurance in Nigeria school system is a goal which learners, teachers, staff and school supervisors aspire to attain. The current school system is characterised by unqualified personnel, dilapidated facilities, poor funding, and cannot allow for effective implementation of e-supervision. The paper concludes that there is need for qualified and ICT-compliant supervisors and supervisees, improved funding of education and political will to drive e-supervision and achieve quality assurance in the school system in Nigeria.